Effect of Physical Exercise On Heart Failure Patients - Wida Sri Kurniyanti; Tuti Herawati; Denissa Faradita Aryani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The incidence of heart failure is a health problem that often occurs in society. Globally it reaches more than 23 million patients worldwide and is expected to grow to 46% by 2030. Patients with heart failure characterized by low activity tolerance, low quality of live, increased mortality and re-hospitalization, and increased treatment cost. Heart failure patients experience shortness of breath, fatigue, anxiety. Where the signs and symptoms of heart failure are chronic and progressive. The writing method uses the PRISMA literature review method, via the remote-lib.ui.ac.id database which facilities a literature search engine and is linked to various scientific publications such as Scopus, ProQuest, Clinical Key for Nursing, PubMed with several keywords, (HFrEF OR (Heart Failure)) AND (physical exercise) AND (Physical capacity). From the first search we get 1512 articles, then selected to become 7 articles with cardiovascular restrictions, last 5 years, nursing, English. Activity management in Heart failure is an important intervention to provide, both while in the treatment room and as self-management and self-care. Non-pharmacological and pharmacological nursing management as a way to improve self-care and self-management in heart failure patients is important to provide because it can increase the achievement of treatment goals.